Quantification of intra-fraction changes during radiotherapy of cervical cancer assessed with pre- and post-fraction Cone Beam CT scans. Issue 3 (December 2015) - Heijkoop, Sabrina T.; Langerak, Thomas R.; Quint, Sandra; Mens, Jan Willem M.; Zolnay, Andras G.; Heijmen, Ben J.M.; Hoogeman, Mischa S.
Abstract: Background and purpose: With the introduction of Intensity Modulated Radiotherapy (IMRT) and image-guided plan-of-the-day strategies, the treatment of cervical cancer has become more sensitive to intra-fraction uncertainties. In this study we quantified intra-fraction changes in cervix-uterus shape, bladder and rectum filling, and patient setup using pre- and post-fraction CBCT scans. Materials and methods: A total of 632 CBCT scans were analyzed for 16 patients with large tip-of-uterus displacement (>2.5 cm) measured in an empty and full bladder CT scan. In all scans, the bladder, cervix-uterus, and rectum were delineated. For rectum and bladder, intra-fraction volume changes were assessed. Systematic cervix-uterus intra-fraction displacements were obtained by non-rigidly aligning the pre-fraction cervix-uterus to that in the post-fraction CBCT. Intra-fraction patient setup changes were obtained by rigidly aligning pre- and post-CBCTs using the bony anatomy. Results: The mean time between pre- and post-fraction CBCT scan was 20.8 min. The group-mean intra-fraction displacements averaged over the cervix-uterus were 0.1 ± 1.4/1.8 ± 1.5/−2.8 ± 1.8 (LR/CC/AP) mm. The group-mean 5th and 95th percentile intra-fraction displacements were −2.3, 2.1/−0.8, 4.9/−5.8, 0.5 (LR/CC/AP) mm. There was a significant correlation between bladder inflow rate and cervix-uterus motion ( r = 0.6 and p < 0.01). Intra-fraction changes in patient setup were 1.3/0.4/0.6 and 1.4/1.0/1.1 mm (LR/CC/AP), for systematic and random changes, respectively. Conclusion: Intra-fraction cervix-uterus motion can be considerable and should be taken into account using appropriate PTV margins.